The impact of reading strategies on EFL students: A research review - Hanita Hanim, Ismail; Yahya Matrouk, Al Raqqad; Kawthar Matrouk, Al Raqqad (2019)
The need to provide appropriate methods of teaching to meet the growing needs of students is increasing as more and more students begin to learn English. This is particularly important for students studying English, who may only be introduced to English in their classroom in a foreign country. Reading strategies have been developed to help learners to resolve language barriers, such as vocabulary and grammar. Teaching reading strategies are proposed as an efficient way of delivering a learning environment that focuses on learners to promote learner independence and develop their language skills. Thirteen research studies were synthesized by means of a Mixed Methods Research Synthesis that collects qualitative and quantitative data, then analyzes them using both qualitative and quantitative approaches. The findings suggest that the evidence does not demonstrate that reading strategies are an effective means for EFL students to improve their comprehension of reading, but it is still uncertain whether certain strategies are better than others. As the results do not provide a particular conclusion on the efficacy of reading strategies, it is concluded that it cannot be helpful to language skills growth by using available class time to teach readings strategies.